1999
DOI: 10.1180/000985599546019
|View full text |Cite
|
Sign up to set email alerts
|

Clay mineralogy at Rothamsted: 1934—1988

Abstract: Soil clay mineralogy at Rothamsted began in the early 1930s, and quickly focused on technique, swelling minerals, micas and sorption phenomena. By the mid-1940s interest had extended to the formation and spatial distribution of soil clays with the move of the Soil Survey of England and Wales to Rothamsted. These themes continued for the next 40 years. Considerable contributions were made to crystal chemistry and structure determinations, and the relationship of these to the sorption and desorption of water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 276 publications
0
3
0
Order By: Relevance
“…Silica is the most considerable elemental content in bentonite; the structure of montmorillonite sheets is arranged by two layers of 2-tetrahedral containing silica and one octahedral layer containing alumina (Loveland, 1999). This silica element can later be used in fertilization in the soil, but because of the strong bonding of the element in bentonite, the breakdown of the structure needs to be done.…”
Section: Spent Bleaching Earth (Sbe) Bentonite As a Source Of Natural Silicamentioning
confidence: 99%
“…Silica is the most considerable elemental content in bentonite; the structure of montmorillonite sheets is arranged by two layers of 2-tetrahedral containing silica and one octahedral layer containing alumina (Loveland, 1999). This silica element can later be used in fertilization in the soil, but because of the strong bonding of the element in bentonite, the breakdown of the structure needs to be done.…”
Section: Spent Bleaching Earth (Sbe) Bentonite As a Source Of Natural Silicamentioning
confidence: 99%
“…Probably chief among these has been potassium, with K-micas apparently providing a labile source of K + (e.g., Norrish, 1973;Loveland, 1984). Loveland et al (1999), in writing a history of clay mineralogy at the Rothamsted Experimental Station from 1934 to 1988, attempted to identify the reasons why considerable effort was put into this area of soil science at one of the world's leading centres of soil research. At its outset in 1934, clay mineralogy was supposed to provide an understanding of the physicochemical behaviour of the soil clay fraction mainly with respect to "the sorption and desorption of water and nutrients, with their practical consequence for soil workability and plant nutrient supply" (Loveland et al, 1999, p. 165).…”
Section: Contributions Of Classical Clay Mineralogy Towards Explanations Of Soil Propertiesmentioning
confidence: 99%
“…An early expectation for clay mineralogy was that it would explain the supply of potassium from soils. In writing a history of the Rothamsted Experimental Station, Loveland et al (1999) nonetheless concluded that clay mineralogy has failed as “a reasonably exact predictive tool” for the potassium‐supplying power of soils. Soils, Plants and Clay Minerals provides a compelling argument for the proposition that clay mineralogy, armed with a more quantitative approach, might now be able to provide a reasonably exact predictive tool for K in soils.…”
mentioning
confidence: 99%